PENYULUHAN PENYAKIT DIABETES DAN PELATIHAN ALAT UKUR GLUKOSA SEDERHANA BAGI GURU MTS WIHDATUL ULUM DESA BONTOKASSI KECAMATAN PARANGLOE GOWA - K, Andi Maulana; Putra, Bayu; Isyanda, Kenanga; Alamsyah, Feri (Jurnal Balireso: Jurnal Pengabdian pada Masyarakat, 2019)
Diabetes mellitus is one of the diseases caused because the individual's lifestyle changes and is notin accordance with the healthy lifestyle produced. Besides that, it is also due to a factor that is acause that cannot be ignored. Knowledge of the wider community in rural areas is minimalbecause it is the cause of public ignorance about diabetes mellitus. The target of this serviceactivity is the father / mother teacher of Mts WihdatulUlumBontokassi village, Gowa. The methodused to achieve the target in this service activity added socialization of service activities by givingquestionnaires to assess the level of knowledge of the target, transfer of reasoned drug use with thelecture method and discussion, use of blood test equipment, control, use of gout, administration ofblood examination equipment to be used in the school environment, and publication of activities injournals or print media. As a result of this service activity, the target of the teacher / teacher in thisservice has increased knowledge about diabetes and how to use self-supporting equipment hasbeen very good than before.